THE MANAGEMENT AND IMPLEMENTATION OF AI IN THE SCHOOL CURRICULUM IN ISRAEL - Loureen HADDAD; Rawia ASHQAR (Annals of the University of Oradea: Economic Science)
This article reviews how Artificial Intelligence (AI) tools are implemented and reshaping the education system in Israel. In many ways Education and AI are intertwined. Education is used as a means to develop minds capable of expanding and leveraging the pool of knowledge, while AI provides tools to develop a more accurate and detailed picture of how the human brain works. By leveraging the best features of machines and teachers, the vision for AI in education is one where AI and teachers work together to achieve the best outcome for students. Since today's students will have to work in a future where AI is a reality, it is important that our educational institutions expose students to the technology and train them how to use it . The idea behind managing and implementing AI is to strengthen student-centred and self-regulated learning and promote the development of students’ information management and problem-solving skills. The study investigates how teachers, school ICT coordinators, principals, and parents deal with the implantation of AI in education, how they use innovative technological tools, and how do they cope with the challenges facing students. In order to be able to integrate AI elements, teachers from the school receive a training course in a coordinated manner. In addition, implementing AI requires schools to assign instructors, who as teachers, hold weekly meetings on digital skills, and each school has a school ICT coordinator and leading teachers on the subject. The role of the principal in this project is to coordinate between the schools and Ministry of Education that supervises how schools implement the project.